Light-Intensity Activity Attenuates Functional Decline in Older Cancer Survivors - Blair, Cindy K. (2014)
While moderate-vigorous intensity physical activities (MVPA) confer the greatest health benefits, evidence suggests that light-intensity activities are also beneficial, particularly for older adults and individuals with moderate-severe comorbidities. PURPOSE: To examine cross-sectional and longitudinal associations between light-intensity activity and physical function in older cancer survivors at increased risk for age- and treatment-related comorbidities, including accelerated functional decline. METHODS: The analysis included data from 641 breast, prostate, and colorectal cancer survivors (54% female) aged 65 and older who participated in a 1-year, home-based diet and exercise intervention designed to reduce the rate of physical function decline. ANCOVA was used to compare means of physical function across levels of PA intensity (low-light (LLPA): 1.5-2.0 METs; high-light (HLPA): 2.1-2.9 METs; MVPA: ≥3.0 METs). RESULTS: In cross-sectional analyses, increasing tertiles of light-intensity activity were associated with higher scores for all 3 measures of physical function (all p-values <0.005), after adjustment for age, sex, BMI, comorbidity, symptoms, and MVPA. Associations were stronger for HLPA than for LLPA. Compared with survivors who decreased or remained stable in MVPA and HLPA at the post-intervention follow-up, those who increased in HLPA, but decreased or remained stable in MVPA, reported higher physical function scores (LSMeans (95% CI): SF-36 physical function subscale: -5.58 (-7.96, -3.20) vs. -2.54 (-5.83, 0.75), p=0.14; basic lower extremity function: -2.00 (-3.45, -0.55) vs. 0.28 (-1.72, 2.28), p=0.07; advanced lower extremity function: -2.58 (-4.00, -1.15) vs. 0.44 (-1.52, 2.40), p=0.01). CONCLUSION: Our findings suggest that increasing light-intensity activities, especially HLPA, may be a viable approach to reducing the rate of physical function decline in individuals who are unable or reluctant to initiate or maintain adequate levels of moderate-intensity activities.